ATP-binding cassette (ABC) import systems of Mycobacterium tuberculosis: target for drug and vaccine development - Dharmendra Kumar Soni; Suresh Kumar Dubey; Rakesh Bhatnagar (Emerging Microbes and Infections)
Nutrient procurement specifically from nutrient-limiting environment is essential for pathogenic bacteria to survive and/or persist within the host. Long-term survival or persistent infection is one of the main reasons for the overuse of antibiotics, and contributes to the development and spread of antibiotic resistance. Mycobacterium tuberculosis is known for long-term survival within the host, and develops multidrug resistance. Before and during infection, the pathogen encounters various harsh environmental conditions. To cope up with such nutrient-limiting conditions, it is crucial to uptake essential nutrients such as ions, sugars, amino acids, peptides, and metals, necessary for numerous vital biological activities. Among the various types of transporters, ATP-binding cassette (ABC) importers are essentially unique to bacteria, accessible as drug targets without penetrating the cytoplasmic membrane, and offer an ATP-dependent gateway into the cell by mimicking substrates of the importer and designing inhibitors against substrate-binding proteins, ABC importers endeavour for the development of successful drug candidates and antibiotics. Alternatively, the production of antibodies against substrate-binding proteins could lead to vaccine development. In this review, we will emphasize the role of M. tuberculosis ABC importers for survival and virulence within the host. Furthermore, we will elucidate their unique characteristics to discover emerging therapies to combat tuberculosis.